2019
DOI: 10.1177/1354067x19894935
|View full text |Cite
|
Sign up to set email alerts
|

Men’s perception of post-marriage body image: Pakistan milieu

Abstract: The present psychological anthropological study tends to explore the perception of single men and their understanding of cultural role regarding post-marriage body between both genders. A qualitative methodology of in-depth interviews and one focus group discussion were employed. The sample included late adolescents (aged 18–24) and early adults (24–34) from Islamabad and Rawalpindi (Pakistan). Purposive sampling was applied and thematic analysis was used as a qualitative paradigm. The number of respondents co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In addition, several gender related norms pressurize spouses in their marriage (Ali et al, 2021) that contribute to problems in understanding. In another study, it was seen that men scored high on relating body image of their spouse as a way of satisfaction in marriage and if not, it generates reasons and drives for having disturbances in marriage (Zubair & Ali, 2021). Another indigenous study showed that those couples who had arranged marriages, unsatisfactory relationship, more restrictions from husbands, and less decision making in home reported more intimidating, chaotic, and confused relationship pattern (Hamid et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several gender related norms pressurize spouses in their marriage (Ali et al, 2021) that contribute to problems in understanding. In another study, it was seen that men scored high on relating body image of their spouse as a way of satisfaction in marriage and if not, it generates reasons and drives for having disturbances in marriage (Zubair & Ali, 2021). Another indigenous study showed that those couples who had arranged marriages, unsatisfactory relationship, more restrictions from husbands, and less decision making in home reported more intimidating, chaotic, and confused relationship pattern (Hamid et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some other strong predictors and problems emphasized having risks of taking marriage to end point quickly were infidelity; physical, emotional, and economic abuse; substance dependency; polygamy; conflict resolution avoidance; ego of partner; birth of baby girl; unreasonable expectation from partner; lack of communication; extended family issues; dowry related violence; taunts; and husband's lack of investment (Ali et al, 2021). In another study, it was found that man's perception about his wife post marriage body image also adds to a significant contributing factor in marital journey (Zubair & Ali, 2021).…”
mentioning
confidence: 99%